2020
DOI: 10.34198/ejms.5221.345363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Radiation on Magneto-hydrodynamics Flow Over an Exponentially Stretching Sheet Embedded in a Thermally Stratified Porous Medium in the Presence of Heat Source

Abstract: The influence of radiation on magneto-hydrodynamics (MHD) boundary layer flow over an exponentially stretching sheet embedded in a thermally stratified porous medium in the presence of heat source and suction/blowing was investigated. Similarity transformation was used to convert the governing equations from partial differential equations into a system of non-linear ordinary differential equations. Solving numerically, we used shooting method along with fourth order Runge-Kutta technique to obtained numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition to this, the theoretical investigations on mixed convection flow of non-Newtonian fluids over a stretching material problem might have enormous economic and energy saving implications for the industries that involve extrusion of molten polymers, hot rolling, food stuffs processing, paper production, and glass fibre production. The Newtonian/non-Newtonian fluid flow problems over a stretching surface in a porous medium have attracted many researchers in recent years [ [19] , [20] , [21] , [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the theoretical investigations on mixed convection flow of non-Newtonian fluids over a stretching material problem might have enormous economic and energy saving implications for the industries that involve extrusion of molten polymers, hot rolling, food stuffs processing, paper production, and glass fibre production. The Newtonian/non-Newtonian fluid flow problems over a stretching surface in a porous medium have attracted many researchers in recent years [ [19] , [20] , [21] , [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the boundary layer thickness reduces with increase in Casson parameter values. Recently, (Senge et al, 2021) investigated MHD flow over an exponentially stretching sheet embedded in a thermally stratified porous medium.…”
Section: Introductionmentioning
confidence: 99%